Kebijakan Ekonomi-Politik Lokal: Studi Pengaruh Pertambangan Galian C Tanpa Izin Terhadap Pendapatan Asli Daerah Kabupaten Kuantan Singingi Tahun 2015-2019 - Aulia Junita; Tito Handoko (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
Cases that occur in Kuansing RegencyMiningin general are Type C mining that is still illegal or not licensed resulting in the exploitation of natural sand and gravel resources by business entities or individuals who do not have permits. The study of local political economy discusses how the local government is able to produce policies on licensing and local tax distribution to mining businesses so that it can become one of the localgovernment revenue. The method in this study is to use literature research and research resources using the study of documents, media and legal products. The results of this study show that the Local Political Economy can develop depending on the results of policies made by the Local Government, for example in mining tax policy and licensing startegi designed as well as the synergy of government and business in the form of kuantan singingi regency government, but in practice there are still many illegal mining and do not have permits, due to the lack of firmness of the Local Government so that people feel free to do mining without having to get permission.